Noun Patterns and Their Vitality in Modern Hebrew - Shatil, Nimrod (2014)
While the number of discontinuous verb morphemes in Modern Hebrew has been determined relatively well (5–7 binyanim), that of their counterparts, discontinuous noun morphemes (mishkalim), ranges in different counts from 100 up to nearly 400. The lower numbers are morphemic while the higher ones include some realizations, many of which do not have discrete functions and therefore cannot be considered discrete morphemes. Besides, cognitive vitality of bulkier systems is limited. Three reductions need to be performed in order to arrive at the real structural and cognitive system of contemporary Hebrew: (a) allomorphic reduction: for example, [ma-o-] (malon) is an allomorph of the morpheme / mi- - a -/ for a certain class of roots; (b) suppletion reduction: for example, the mishkalim / - a- o- / (gadol) and / - a - u - / (pašut) constitute one unit (morpheme), since no root interdigits with both, and since they have one function, that is, forming adjectives; (c) nonproduction reduction: cognitively, only productive mishkalim, whose proved number is around 30, are part of the inner system of the speakers. All others, like / ta - - e -/ (tašbec), are to be considered as mere inherited loans from former layers. The whole system can be depicted as a core of about 30 real morphemes, with all other related forms organized in concentric circles around them.